Using the virtual-abstract instructional sequence to teach addition of fractions. (November 2017) - Bouck, Emily C.; Park, Jiyoon; Sprick, Jessica; Shurr, Jordan; Bassette, Laura; Whorley, Abbie
Highlights: Students learned to independently add fractions with unlike denominators. Students maintained of adding fractions with unlike denominators skills, but were less successful than during intervention. The use of a representational phase may not be necessary for students to acquire mathematical skills involving fractions. Abstract: Background/aims/methods: Limited literature examines mathematics education for students with mild intellectual disability. This study investigated the effects of using the Virtual-Abstract instructional sequenceto teach middle school students, predominantly with mild intellectual disability, to add fractions of unlike denominators. Researchers used a multiple probe across participants design to determine if a functional relation existed between the Virtual-Abstract instructional sequence strategy and students' ability to add fractions with unlike denominators. Procedures/outcomes: The study of consisted of three-to-nine baseline sessions, 6–11 intervention sessions, and two maintenance sessions for each student. Data were collected on accuracy across five addition of fractions with unlike denominators problems. Results/conclusions: The VA instructional strategy was effective in thestudents to add fractions with unlike denominators; a functional relation existed between the VA instructional sequence and adding fractions with unlike denominators for three of the four students. Implications: The Virtual-Abstract instructional sequencemay be appropriate to support students with mild intellectual disability in learning mathematics, especially when drawing or representing the mathematical concepts may prove challenging.